Kingsley Amis’s Lucky Jim: A Parody on Changing Social Order in Post War England - Tanu Bura , Dr. Ramandeep Mahal (International Journal of Advanced Science and Technology, 2020)
The 1950s, a period following the Second World War, was actually the beginning of an era which extends to date when class identity by virtue of birth and upbringing in England was overcome by individual achievement and social mobility between class levels. Importance of class identity is diminishing in all modern societies where access to education becomes the prime reason for social mobility. Amis in his works generally deals with the restructuring of British society post World War II. One of the effects was seen in the English education system where educational opportunities were opened to the youth of the working and middle classes. The advent of provincial universities and the declining influence of the culturally elite led to social friction between both the classes. During the 1950s England actually witnessed a period of prosperity which percolated to an emerging middle-class and also (to a certain extent) the working-class. Expanding higher educational opportunity suddenly gave a jump to the social mobility of these classes. This period has actually quite a few authors who emerged and expounded narratives which were effective in describing the social effect that this war had upon society. The expression "Angry Young Man" was not used or related to the gathering until after John Osborne’s play Look Back in Anger had been distributed. However a portion of the essayists who are regularly related with the term achieved lime light as a result of the quickness of their works being distributed. Amis can be described as one of them. This work of his represents the conflict inside the then scholarly world and elaborates on the social and political air of the College through it in comic terms.